Representations of the female gender in selected local teen magazines a content analysis - Ramos, Maria Carmina B. (2007)
The glossy magazine industry in the Philippines is a fast-faced, growing business. Leading local teen magazine titles such as Candy, MEG and Seventeen Philippines, in particular, reach a large young Filipina audience. This same audience is also part of the patron communities of academic libraries in local schools. It is with this in mind that this content analysis was undertaken.